Soil physical properties and oil palm growth performance as influenced by continuous tractor traffic compactions - Hasnudin, Hazira (2023)
Changes in soil physical properties due to compaction have always been underestimated in their effects on oil palm growth. Hence, an extensive 90-month period trial was carried out to quantify the influence of various compaction intensities on soil physical properties, nutrient uptake, as well as oil palm growth responses, and yield. This research was carried out at the Malaysian Palm Oil Board (MPOB) Keratong Research Station, Pahang, where oil palm was planted on the inland sandy clay loam type of soil. In 2013, the experimental site was planted with the DxP AVROS variety at a density of 148 palms per hectare. The compaction treatments, comprising a tractor towing a trailer weighing 2 tons (T1), 4 tons (T2), and 8 tons (T3), and a control plot (no vehicle traffic), were commenced in 2014, at the palm age of 18 months. The vehicle traffic treatments were operated three times per month. The soil physical analyses and vegetative measurements were done twice, at 6-month intervals per year, whereas the yield components were recorded monthly when the oil palm trees reached 3 years old. From this study, it was found that the soil bulk density was significantly impacted by the weighing treatments after 90 months of compaction. Apparently, the mean soil bulk density in compacted plots, under wheel track area, and at 0–10 cm depth was higher by approximately 2.9%, 2.0%, and 0.7 to 1.5%, respectively, as compared to the control plots, frond pile area, and 10–20 cm and 20–30 cm soil depths. In contrast, the mean total porosity was significantly decreased by 3.9% in the compacted plots, lowest at the under-wheel tracks area by 47.2%, and significantly higher by 0.5 to 1.5% at the 0–10 cm depths. The soil compaction was further indicated by an increment of available water in compacted soil up to 120%. The soil hydraulic conductivity and infiltration rate were significantly reduced in compacted plots by 6.5 to 14.9% and 9.9 to 20.8%, respectively. It was found that the frond pile area recorded 17.0% and 14.8% higher soil hydraulic conductivity and infiltration rate, respectively, as compared to the wheel track area. Notably, there were no significant differences in nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg) concentrations in the control and all compacted plots, indicating that the nutrient availability was not affected by the compacted soil due to the heavy vehicle traffic. The fresh fruit bunch (FFB), bunch numbers, and weight were significantly higher in compacted plots as compared to the control. Nonetheless, the oil palm standing biomass in control plots was 3.52% significantly higher as compared to the compacted plots. The findings also demonstrate that there were insignificant differences between trunk heights in all treatments. However, the palm in compacted plots exhibited a significant reduction in trunk diameter, trunk dry weight, and petiole-cross section. The total leaf area and LAI value of palms in compacted plots were significantly higher by 1.0 to 8.0% as compared to the control. Evidently, the current findings indicate that, regardless of weight, the 90-month compaction treatments had impacted soil properties but did not become a limiting factor to palm production because a positive association between these treatments and oil palm yield was observed, supported by no significant difference in foliar nutrient content between treatments in this study.